Identification of Eruption Centers, Volcanic Products, Vegetation Stress, and Lineament Structures in the Mount Raung Geothermal Prospect Area Using Landsat-8 and Sentinel-1A Data Processing - Maulida, Nanda Hanyfa (Universitas Khairun, 2025)
Mount Raung is one of the active volcanic mountains which have geothermal potential. To investigates the Mount Raung geothermal prospect area in East Java, Indonesia, we use remote sensing method with Landsat-8 and Sentinel-1A data. The analysis focuses on identifying eruption centers, mapping volcanic products, assessing vegetation stress, and delineating lineament structures to provide an initial overview of the prospect zone in the area. Remote sensing methods were applied through image processing techniques including NDVI analysis, optical band composites, and radar-based structural mapping. The results indicate that Mount Raung has a large, dry caldera with multiple eruption centers and significant volcanic deposits. Several areas showed vegetation stress, potentially linked to surface geothermal manifestations. Structural analysis using SAR data revealed high lineament density, especially in the southwestern and southern regions of Mount Raung, which also coincide with vegetation stress zones. These areas are considered to have high geothermal potential due to favorable permeability conditions. The integration of optical and radar data expected to be an effective approach in the preliminary exploration of geothermal resources.